IMPROVING CONSUMER RIGHTS PROTECTION MECHANISMS IN UZBEKISTAN’S AUTOMOBILE DELIVERY SYSTEM: LEGAL FRAMEWORKS AND DIGITAL TRANSFORMATION DIRECTIONS (Marketing Journal, 2025)
This article examines the current state of consumer rights protection in Uzbekistan’s automobile delivery system, focusing on regulatory compliance, warranty disparities, service infrastructure, and digital transparency. Based on consumer complaints record ed between January and August 2025, the study identifies recurring issues such as untimely vehicle delivery, insufficient warranty coverage, lack of Uzbek -language user information, and the absence of unified digital monitoring for after-sales services. Us ing national legislation and empirical field data, the study proposes an integrated model for enhancing consumer confidence through digital service book systems, unified online registries, and insurance -based warranty mechanisms. The findings emphasize the importance of harmonizing warranty policies, introducing electronic monitoring tools, and ensuring transparency and linguistic accessibility in the automotive market, in alignment with the “Digital Uzbekistan – 2030” national strategy.
Keywords: consumer rights; automobile market; digital warranty systems; after - sales services; service centers; delivery delays; digital economy; competition policy